Methodology to perform simulation experiments for realistic VANET scenarios using open source software tools - SINGH, G.D.; PRATEEK, M.; SASTRY, G.H. (International Journal of Psychosocial Rehabilitation, 2020)
Simulation software has made testing and training much cost effective and result oriented. Many fields are now depending on simulation results for their real-time product deployments. Vehicular Ad hoc Network is one of the recent emerging domain where simulation has played a very significant role. In this research paper, we have discussed our methodology that has used during our various research experiments to analyze VANET performance results. The most difficult aspect of simulation tests is deciding the software tools to perform the experiments. We have also presented features of our opted open source software tools that can used with ease by the research communities for their VANET simulations. Hence, this paper is a contribution that enables to decide which software tools are beneficial for realistic VANET scenario simulations.